Adenomyoma causing gastric outlet obstruction - Kambiz Kamrani; Jessica Cutler; Charlotte Austin; Rachel Hudacko; Nishith Bhattacharyya (Elsevier, 2019)
We report an adenomyoma in a 15-year-old girl with an obstructing pyloric mass. Histologic examination of the resected specimen showed irregular glands and smooth muscle cells consistent with adenomyoma. Our review of the literature showed seven other similar pediatric cases where these hamartomas mimic the presentation of hypertrophic pyloric stenosis as well as duplication cysts radiographically and are difficult to biopsy endoscopically. While rare, gastric adenomyomas are benign but require complete surgical resection for diagnostic clarity and therapeutic resolution of obstruction. Keywords: Gastric adenomyoma, Gastric outlet obstruction